2020
DOI: 10.1002/elan.202060059
|View full text |Cite
|
Sign up to set email alerts
|

Hollow Reticular Shaped Highly Ordered Rice Husk Carbon for the Simultaneous Determination of Dopamine and Uric Acid

Abstract: We have prepared activated porous carbon material through simple pyrolysis method from rice husks (rhAC) for sensitive detection of dopamine (DA) and uric acid (UA). The prepared rhAC material was thoroughly characterized using various spectroscopic, microscopic, and electroanalytical techniques. Analysis of the voltammetric data showed that the analytes followed a first order reaction kinetics while following a 2e−/2H+ transfer process. We have discussed the possible oxidation mechanism for the analytes based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…Considering the various applications of the AC, producing a cost-effective AC from industrial waste or organic waste as a source material is being actively considered by the scientific community. Several organic waste materials, such as peanut and coconut shell, [62] fruit stone and nutshell (almond, hazelnut, walnut shell, and apricot stone), [63] date palm leaves, [64] shells of lentil, wheat, and rice, [65] Albizia procera leaves, [66] orange and banana peel, [67] citrus fruits, [68] tal palm leaves, [69] mango peel, [70] garlic peel, [71] potato peel, [72] cucumber peel, [73] rice husk, [74] rice straw, [75] jute sticks and leaves, [76] sugarcane bagasse, [77] willow tree legs, [78] aloe vera green waste, [79] olive leaf, [80] jute sticks, [81] bamboo waste, [82] and other waste materials have been utilized for the generation of cheap AC for the removal of various environmental pollutants. The porous structure of AC from different source materials is shown in Figure 9.…”
Section: P E R S O N a L A C C O U N T T H E C H E M I C A L R E C O R Dmentioning
confidence: 99%
“…Considering the various applications of the AC, producing a cost-effective AC from industrial waste or organic waste as a source material is being actively considered by the scientific community. Several organic waste materials, such as peanut and coconut shell, [62] fruit stone and nutshell (almond, hazelnut, walnut shell, and apricot stone), [63] date palm leaves, [64] shells of lentil, wheat, and rice, [65] Albizia procera leaves, [66] orange and banana peel, [67] citrus fruits, [68] tal palm leaves, [69] mango peel, [70] garlic peel, [71] potato peel, [72] cucumber peel, [73] rice husk, [74] rice straw, [75] jute sticks and leaves, [76] sugarcane bagasse, [77] willow tree legs, [78] aloe vera green waste, [79] olive leaf, [80] jute sticks, [81] bamboo waste, [82] and other waste materials have been utilized for the generation of cheap AC for the removal of various environmental pollutants. The porous structure of AC from different source materials is shown in Figure 9.…”
Section: P E R S O N a L A C C O U N T T H E C H E M I C A L R E C O R Dmentioning
confidence: 99%
“…The prepared sensor demonstrated a linear response in the dopamine concentration range from 0.5 µM to 250 µM with a limit of detection of 0.25 µM. Similarly, Haque et al (2020b) reported hollow reticular-shaped ADCs derived from rice husks for uric acid and dopamine simultaneous detection. The possible oxidation mechanism for the analytes was discussed in detail, and the sensor was tested for stability, reproducibility, and interference.…”
Section: Applications Of Adcmentioning
confidence: 64%
“…This indicates that the preparation of valuable and useful ADCs is important. ADCs are extensively used in different fields, including sensing (Aziz et al, 2020;Ahammad et al, 2019a;Ahammad et al, 2019b;Ahammad et al, 2018;Haque et al, 2020a;Aziz et al, 2017;Haque et al, 2020b), microbial fuel cells (Senthilkumar et al, 2020), filtration/separation (Aziz et al, 2019;Khan et al, 2020), oil recovery (Haq et al, 2019), electrochemical water splitting (Shah et al, 2019;Buliyaminu et al, 2020), electrode materials for supercapacitors (Mohamedkhair et al, 2020;Islam et al, 2020;Shah et al, 2020;Deb Nath et al, 2019;Aziz et al, 2020), and in other emerging technology applications. In addition, unique properties of the ADCs like versatile porosity, high specific-surface-area (SSA), and high electrical and thermal conductivities attracted much attention of the researchers to utilize them in various applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6,8,11] The unique properties of these agriculturalproduct-derived materials include their carbon-like high-surface area, versatile porosity, and high electrical and thermal conductivity, allowing them to be used in many different applications. Various agricultural byproducts such as date palm leaves, [4,12,13] tal palm leaves, [14] Albizia procera leaves, [15][16][17] Syzygium cumini leaves, [8] taro stems, [18] rice husks, [19] Pithophora polymorpha, [20] tomato stems, [21] barley straws, [22] sunflower piths, [23] lotus stalks, [24] peanut shell, [25] carrot residue, [26] citrus fruits, [27] and orange peel [28] have been used as suitable precursors for the production of low-cost carbonaceous materials.…”
Section: Introductionmentioning
confidence: 99%